The development of the support system for students with visual impairment in higher education institutions - Jatunam, Tam; Chai-aroon, Teeradej; Kachondham, Pimpa; Borvornsompong, Pairuch (Kasetsart Journal of Social Sciences, 2021)
This research was to examine the current situation of support services available for students with visual impairment in higher education institutions and to propose the guidelines for improvement of support services available for students with visual impairment in higher education institutions. The participants were 227 undergraduate students with visual impairment, 46 university staff, and five university administrators. The research instruments included two sets of questionnaires for staff and undergraduate students, and the interview questions for university administrators. While quantitative data were analyzed through descriptive statistics and cluster analysis, qualitative data were analyzed with content analysis and grouping technique, and used narrative approach in reporting the results. The results showed that current situation of support services available could be categorized into three levels: high support system—high potential to provide support services, medium support system—medium potential to provide support services, and low support system—low potential to provide support services. However, all three groups provided high social and financial support, and medium physical support. The results also found that students with visual impairment needed essential support and were able to access support services in five domains including social, financial, physical, general support, and testing accommodation. In fact, the university administrators have adopted the policies of the Higher Education Commission by establishing Disability Support Service Centers as well as including support services for students with disabilities as a part of educational quality assurance.